Peran Guru Pendidikan Kewarganegaraan dalam Mengembangkan Nilai Moral yang Terkandung di dalam Materi Demokrasi di Kelas VIII Sekolah Menengah Pertama Negeri 1 Sungai Raya Kepulauan Kabupaten Bengkayang - Firmansyah, Syarif (Lambung Mangkurat University Indonesia, 2017)
Basically the acquisition of moral values is seen as the regeneration of the traits of a person. It can be said that the moral values as continuity of psychological processes such as perception, attitude, and belief in oneself. On the other hand, some are saying that the acquisition of moral values as the social interaction between the individual and his environment. Current perspective is more emphasis on the role of the outside world as a factor that facilitates value system. The role of parents, teachers, community and moral value system that is maintained in an environment in which he lives is an important factors for the possession of the moral values of the individual self. In the view of philosophy, moral values are often associated with the problem of goodness. Something is said to have a moral value if something is useful, true (truth value), beautiful (aesthetic value), good (moral values), religious (religious values), and so forth. Moral values and the ideal is something that is good. Hence the value is regarded as something abstract and can not be touched by the five senses. In connection with this, the Fraenkel (in Hamid Darmadi, 2007: 27) states that this nilaimoral presence in the